2023
DOI: 10.1186/s12978-023-01563-6
|View full text |Cite
|
Sign up to set email alerts
|

Stigma of infidelity associated with condom use explains low rates of condom uptake: qualitative data from Uganda and Tanzania

Abstract: Despite widespread messaging supporting male (external) condom use to prevent HIV in endemic settings, utilization of condoms is low across sub-Saharan Africa. A thorough understanding of barriers to condom use as a form of HIV prevention is necessary to reduce HIV transmission. Here, we present qualitative data from rural eastern Africa to explain low utilization of condoms among heterosexual adults. Focus groups and interviews were conducted in Tanzania and Uganda between 2016 and 2019. A content analysis ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…, number of living children and desire for additional children play an important role in determining the use of family planning. The study also showed that when mothers were asked if the condom would disappear into the vagina, the majority 129(93.5%) thought that the condom could not disappear into the vagina, and only 9(6.5%) of the mothers thought it could, the study shows a good attitude on mothers on condom use, since most of them are aware the condom doesn't disappear during intercourse, this would build in confidence in mothers to utilize a condom as a family planning method, when this study is compared with other studies, the study shows a difference from a study by Broderick et al, [31] who showed that in Uganda, 4 in 50 cohort group members believed that it was potentially dangerous to use condoms because it could get stuck in the vagina cause damage. A negative attitude toward family planning is associated with rumours and myths about family planning methods and can prevent young people from seeking family planning.…”
Section: Discussion Knowledge Of Family Planning and Its Utilizationcontrasting
confidence: 58%
“…, number of living children and desire for additional children play an important role in determining the use of family planning. The study also showed that when mothers were asked if the condom would disappear into the vagina, the majority 129(93.5%) thought that the condom could not disappear into the vagina, and only 9(6.5%) of the mothers thought it could, the study shows a good attitude on mothers on condom use, since most of them are aware the condom doesn't disappear during intercourse, this would build in confidence in mothers to utilize a condom as a family planning method, when this study is compared with other studies, the study shows a difference from a study by Broderick et al, [31] who showed that in Uganda, 4 in 50 cohort group members believed that it was potentially dangerous to use condoms because it could get stuck in the vagina cause damage. A negative attitude toward family planning is associated with rumours and myths about family planning methods and can prevent young people from seeking family planning.…”
Section: Discussion Knowledge Of Family Planning and Its Utilizationcontrasting
confidence: 58%
“…The narrow and overall negative focus on sexual relations and condom use found within our study highlights the stigma and discrimination associated with condom use both within the Timorese health system and broader society. Stigma and discrimination associated with condom use has also been described in other contexts, with similar associations identified between condom use and infidelity, promiscuity and lack of love or trust in a relationship [ 34 36 ]. Numerous social harms, such as reputational damage, associated with condom use have been described in other contexts as especially impacting young people and women [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 87%
“…This implies that condom use is widely recognized as an effective barrier method to reduce the risk of sexually transmitted infections, including HIV. In contrast, [49] uncovered that condom use has been stigmatized as indicators of unfaithfulness. Additionally, the study conducted by [50] indicated that healthcare workers believed the absence of female condoms played a role in insu cient utilization.…”
Section: Discussionmentioning
confidence: 99%